Developmental Evaluation (Tamarack Community, 2012)
This webpage from Tamarack Community provides links to audio files of an interview between Mark Cabaj and Michael Patton in which they discuss the topic of development evaluation. This is an "approach that has proven particularly useful and effective at addressing the unique challenges of evaluating the real nature of community change work. Learning Objectives: To deepen appreciation for the role of evaluation and evaluation thinking To explore the distinctions between various types of evaluation To understand more about developmental evaluation and its use To investigate concepts, tools and resources available to support working with developmental evaluation methods" (Tamarack Community)